Traits of the Russian information warfare - Martišius, Mantas (Information & Media, 2015)
This article discusses the Russian theorists’ approach to information warfare, its applicability to regain the Soviet Union “lost territories”. Reviewed is the juridical background to consolidate the electronic media in the hands of the Russian government. The process of elimination alternative political opinions in Russia is reviewed. Discussed are the thoughts of Russian information warfare theorists about the media used to collect the areas considered as their own. The ways how the media can create the imaginary reality are examined. Russia’s state-controlled information space overcomes Russian boundaries and enters the global information space. The information war is not a very new phenomenon. The current military affairs have been led by information war activities. Protests against the former Ukrainian president Viktor Janukovich started in late 2013 and concluded in the open revolt and overthrow of the existing regime. Discontent with such events, Russia brutally intervened in the internal Ukrainian affairs, occupied and annexed the Crimean peninsula, then provoked mutiny in estern Ukrainian regions. The war broke out, and the Russian media have been exploited to legitimize Kremlin’s and separatists actions. The purpose of the article is, by using analytical and comparative methods, to scrutinize the information war problematic in Russian’s works. Information space exploitation is a crucial Russian politics’ part. The consolidated and censored internal Russian media space is designed to consolidate society to support nationalistic and imperialistic Moscow ambitions and to prevent other than Kremlin ideas’ circulation. The information war is used to penetrate into the former Soviet Union republics’ media space, to form the media agenda, and to shape, now independent from Russia states societies’ views. Even more, Russia creates channels for non-Russian speakers to attract them to their side. The Russian media directly or by exploiting close relationships with Moscow business, construct the image of the favourable reality. The complicated social problems have led us to the fact that decision currently is made on the media supplied facts’ preferences. The perceptions of ideas is constructed in the information war twilight. The article also draws attention to fact that Lithuania is abjectly prepared to react to the external information war threat from Russia. Russia wisely uses the EU legislation loops into the penetrate to Lithuanian media space and to guarantee the EU law protection and contrary to Russia internally wiped out media field from the non-Kremlin-controlled media. The juridical posed law makes obstacles for foreign capital to invest in the Russian media. And the media which get grants from abroad is claimed to be foreign agents. Lithuania is very concerned about the information war influence on society, but the internal media business practices, the principles of electronic media regulations, and being so late to react do not allow to take effective contra measures. Lithuania has successfully intergraded into political, military, and economic western alliances, but not to the western media space. This fact allows Russia still to fight for Lithuanian hearts and souls.